2017
DOI: 10.1016/j.ultsonch.2017.03.046
|View full text |Cite
|
Sign up to set email alerts
|

Modifying the physicochemical properties of pea protein by pH-shifting and ultrasound combined treatments

Abstract: The effect of a pH-shifting and ultrasound combined process on the functional properties and structure of pea protein isolate (PPI) was investigated. PPI dispersions were adjusted to pH 2, 4, 10, or 12, treated by power ultrasound for 5min, and incubated for 1h before the sample pH was brought back to neutral. After treatment, water solubility, protein aggregate size, solution turbidity, surface hydrophobicity (Ho), free sulfhydryl content (SH), and sodium dodecyl sulfate polyacrylamide gel electrophoresis (SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
174
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 355 publications
(201 citation statements)
references
References 33 publications
26
174
1
Order By: Relevance
“…The unsonicated soy proteins and ultrasonicated proteins at higher and lower PD had generally similar protein subunit electrophoretic patterns, suggesting that sonication did not change the protein profiles for soy protein regardless of sonication conditions. Similar results were observed by Wang et al [41] and Karki et al [10] who also reported no modification in soy protein profiles. Kidney bean protein consists of phaseolin and chickpea protein consists of legumin and vicilin as a major protein subunit; these can be seen in the gel as major bands (Fig.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 90%
See 1 more Smart Citation
“…The unsonicated soy proteins and ultrasonicated proteins at higher and lower PD had generally similar protein subunit electrophoretic patterns, suggesting that sonication did not change the protein profiles for soy protein regardless of sonication conditions. Similar results were observed by Wang et al [41] and Karki et al [10] who also reported no modification in soy protein profiles. Kidney bean protein consists of phaseolin and chickpea protein consists of legumin and vicilin as a major protein subunit; these can be seen in the gel as major bands (Fig.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 90%
“…There was significant (p < 0.05) increase of free SH in chickpea protein from 6.76 ± 0.39 μmol g -1 to 20.40 ± 4.94 μmol g -1 at higher PD sonication. This finding suggests that HPS could break the disulfide bonds (i.e., can cause the reduction of S-S linkage to form free -SH groups), which exposes the sulfhydryl group to the surface of proteins [16,41]. The buried sulfhydryl group of proteins when exposed to high pressure and sheer force of cavitation phenomenon might lead to an increase in the free sulfhydryl group.…”
Section: Free Sulfhydryl Content Of Final Protein Productsmentioning
confidence: 97%
“…For a true solution, protein particle size is likely to be ≤1 nm. Therefore, reducing protein size generally improves its solubility (Jiang et al, ; Kong, Zhou, & Qian, ; Zheng et al, ). Acid/alkali or enzymatic hydrolysis has been used to decrease protein molecular weight/size, thereby increasing protein solubility (Wouters, Rombouts, Fierens, Brijs, & Delcour, ).…”
Section: Factors That Influence Protein Solubilitymentioning
confidence: 99%
“…The wall materials used affect the stability of emulsion and further affect the process efficiency and properties of the resulting microcapsule powders . Usually, no single wall material can lead to all the required properties especially high encapsulation efficiency of the active material, so composite wall materials are often utilized in the process . Studies have shown that a combination of carbohydrates as matrix materials can effectively improve the encapsulation efficiency .…”
Section: Introductionmentioning
confidence: 99%